The Implementation of Technology in Facilitating Interprofessional Team Communication in Emergency Cases: Implementation of Technology in Facilitating Interprofessional Team Communication in Emergency Cases - Sumihar, Rotua (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
The implementation of technology in interprofessional team communication in emergency cases plays a crucial role in ensuring effective and timely coordination. Technological advancements such as telemedicine, mobile applications, and artificial intelligence-based decision support systems significantly enhance information exchange, decision-making, and patient care outcomes. This article discusses various technological tools utilized in emergency situations and their impact on interprofessional communication in the healthcare sector. Additionally, this paper explores challenges in implementing technology and strategies to optimize its use. This research employs a literature review approach, examining various studies on technology in medical team communication in emergency settings. Data were collected from scientific journals, research reports, and publications from health organizations. The study results indicate that technologies such as telemedicine, mobile communication applications, and artificial intelligence-based decision support systems have improved the speed and accuracy of interprofessional communication in healthcare facilities. The use of electronic health records (EHR) also provides benefits by facilitating real-time access to patient information. In conclusion, the implementation of technology in interprofessional team communication in emergency cases has a positive impact on improving coordination effectiveness and patient safety. However, optimizing the use of technology still requires support from various stakeholders, including medical personnel, healthcare institutions, and policymakers.